Mini-Review: Bioactivities of Bacterial Cell Envelopes in the Central Nervous System - MacCain, William J.; Tuomanen, Elaine I. (Frontiers in Cellular and Infection Microbiology, 2020)
During acute bacterial meningitis, recognition of the bacterial envelope by immune cells of the central nervous system (CNS) generates a robust response that is essential to clear bacteria. This response is further amplified during treatment when lytic antibiotics, required for cure, also generate a burst of highly inflammatory cell envelope debris. Different peptidoglycan (PG) subcomponents interact with neurons, glia, and the blood brain barrier resulting in the entire symptom complex of meningitis. Recently, this CNS-cell envelope signaling axis has been extended to non-inflammatory recognition of cell wall components circulating from endogenous bacteria to the brain resulting in both benefit and chronic damage. This review will describe the molecular details of a broad array of cell envelope-induced responses in the CNS and what current strategies can be implemented to improve clinical outcome.